Hunters and hunting across indigenous and colonist communities at the forestagriculture interface: an ethnozoological study from the Peruvian Amazon - Francesconi, Wendy; Bax, Vincent; Blundo Canto, Genowefa M.; Willcock, Simon P.; Cuadros, Sandra; Vanegas, Martha; Quintero, Marcela; Torres Vitolas, Carlos A. (Springer, 2018)
Background: Wildlife has been traditionally used by forest communities as a source of protein, and the Peruvian Amazon is no exception. The articulation of colonist and indigenous communities to urban centers and markets results in changes in livelihood strategies and impacts on wildlife populations. To address the threat of overhunting and forest conversion, we provide a generalized characterization of colonist and indigenous communities and their hunting activities near Pucallpa, Ucayali, Peru. Methods: A semi-structured household survey was conducted to characterize hunters and describe their prey collections. The data were analyzed by conducting a Kruskal-Wallis test, a multiple regression analysis, and by estimating the harvest rate (H). Results: Less wealthy households were more actively engaged in hunting for food security and as a livelihood strategy. Additionally, older hunters were associated with higher hunting rates. Although the percentage of hunters was relatively low, estimated hunting rates suggest overharvesting of wildlife. Lowland pacas (Cuniculus paca) were the most frequently hunted prey, followed by red brocket deer (Mazama americana) and primates. While hunting intensity was not significantly different between indigenous and colonist communities, hunting rate disparities suggest there are different types of hunters (specialized vs. opportunistic) and that prey composition differs between communities. Conclusion: Close monitoring of wildlife populations and hunting activities is ideal for more accurately determining the impact of hunting on wildlife population and in turn on forest health. In lack of this type of information, this study provides insight of hunting as a shifting livelihood strategy in a rapidly changing environment at the forest/agriculture frontier.